2003
DOI: 10.1021/bi034870f
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Tescalcin, a Novel EF-Hand Protein with a Single Ca2+-Binding Site:  Metal-Binding Properties, Localization in Tissues and Cells, and Effect on Calcineurin

Abstract: The tescalcin gene is preferentially expressed during mouse testis differentiation. Here, we demonstrate that this gene encodes a 24 kDa Ca(2+)- and Mg(2+)-binding protein with one consensus EF-hand and three additional domains with EF-hand homology. Equilibrium dialysis with (45)Ca(2+) revealed that recombinant tescalcin binds approximately one Ca(2+) ion at physiological concentrations (pCa 4.5). The intrinsic tryptophan fluorescence of tescalcin was significantly reduced by Ca(2+), indicative of a conformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
115
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(121 citation statements)
references
References 45 publications
(89 reference statements)
6
115
0
Order By: Relevance
“…The testican gene turned out to be expressed mainly in stellate cells of the cerebellum. We selected 14 genes from the previous study and three additional TTXsuppressive genes which were identified in this study and expressed in the mature cerebellum (10)(11)(12). PCR analysis confirmed that the expression of all 17 genes was inhibited by TTX to different degrees, ranging from 15-85% ( Fig.…”
Section: Resultsmentioning
confidence: 62%
“…The testican gene turned out to be expressed mainly in stellate cells of the cerebellum. We selected 14 genes from the previous study and three additional TTXsuppressive genes which were identified in this study and expressed in the mature cerebellum (10)(11)(12). PCR analysis confirmed that the expression of all 17 genes was inhibited by TTX to different degrees, ranging from 15-85% ( Fig.…”
Section: Resultsmentioning
confidence: 62%
“…Tesc encodes a putative EF-hand Ca 2ϩ -binding protein. It shares sequence and functional homology with calcineurin-B homologous protein (CHP), which can inhibit the phosphatase activity of calcineurin A, which regulates the NFAT nuclear translocation and activation (53,54).…”
Section: Discussionmentioning
confidence: 99%
“…To further study if Ca 2þ binding by the EF-hand motifs of the N-terminal region of rbohB is involved in Rac1-rbohB interaction, we mutated the conserved EF-hand motifs of Os rbohB, substituting the Asp residues at positions 242 and 286, generating the mutants OsrbohB D242A (ef1) and D286A (ef2) (Gutierrez-Ford et al, 2003). Mutations in these conserved Asp residues, which participate in Ca 2þ coordination, are known to disrupt Ca 2þ binding (see Supplemental Figure 3 online).…”
Section: Derepression Of Ca 21 -Mediated Inhibition Of Os Rac1-rbohb mentioning
confidence: 99%